The Impact of Natural Resource Exploitation on Balanced Development with Modified Reproduction Scheme Based on Supply Chain Management - Yadulla Hasanli; Nazim Hajiyev; Fail Kazimov (International Journal of Supply Chain Management, 2019)
In the scientific work has been modified the impact of the exploitation of natural resources (non-renewable oil and gas reserves) on balanced economic development and been researched Karl Marx's production scheme. Marx's simple and extensive reproduction scheme based on supply chain management, rather I-capital sector was divided into 3 parts for physical, natural and human capitals, and at first, theoretically modified and analyzed added value from the exploitation of natural capital (oil and gas reserves). The literature review, results, and statistical figures of carried out necessary research have been substantiated. The result of analysis proved that the added value generated from the exploitation of oil and gas resources mainly in the consumer sector has created additional demand and as a result, have emerged the interdisciplinary demand and supply sequences. In the scientific work carried out analysis of the results obtained from the model of realization and are given specific directions and calculations of creating balanced development of revenues received from exploitation oil and gas resources.